2014
DOI: 10.1017/s1478951513001107
|View full text |Cite
|
Sign up to set email alerts
|

Support for families of patients dying with dementia: A qualitative analysis of bereaved family members' experiences and suggestions

Abstract: Family members face multiple burdens while caring for their demented relatives and need more professional support during the course of the disease trajectory as well as in the terminal phase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
91
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(92 citation statements)
references
References 26 publications
1
91
0
Order By: Relevance
“…Topics: characteristics of an ideal dementia-specific community care service, the ideal outcomes or achievements of a dementia-specific community care service. 2013/ Singapor [89]Vaingankar et al63 informal CGs; 60% female20% spouse; mean age = 52.9 yearsTen focus group and 12 semi-structured interviews (funnel approach). Topics: experiences and discussion focused on each identified unmet needs or challenges. 2014/ Germany [90]Muders et al85 CGsQuestionnaire with two open-ended questions. Topics: exploration and documentation of the CG’s needs and identification of the healthcare professionals to adequately support them. 2015/ USA [91]Meyer et alTen vietnamese informal CGs; seven female; two spouse; mean age = 55Semi-structured interviews ( n  = 10 CGs).…”
Section: Resultsmentioning
confidence: 99%
“…Topics: characteristics of an ideal dementia-specific community care service, the ideal outcomes or achievements of a dementia-specific community care service. 2013/ Singapor [89]Vaingankar et al63 informal CGs; 60% female20% spouse; mean age = 52.9 yearsTen focus group and 12 semi-structured interviews (funnel approach). Topics: experiences and discussion focused on each identified unmet needs or challenges. 2014/ Germany [90]Muders et al85 CGsQuestionnaire with two open-ended questions. Topics: exploration and documentation of the CG’s needs and identification of the healthcare professionals to adequately support them. 2015/ USA [91]Meyer et alTen vietnamese informal CGs; seven female; two spouse; mean age = 55Semi-structured interviews ( n  = 10 CGs).…”
Section: Resultsmentioning
confidence: 99%
“…7 The existing evidence shows that higher rates of anxiety and depression on the family caregivers of people with dementia are likely to be found when compared with caregivers of people without this health problem. [8][9][10] Evidence also shows that despite the caregivers' exhaustion and physical burden, they constantly delay seeking help and neglect their own health. 11 The level of family burden caused by dementia, even in the early stages, is recognized as a public health problem.…”
Section: Introductionmentioning
confidence: 99%
“…11 The level of family burden caused by dementia, even in the early stages, is recognized as a public health problem. 10 The increasing caregivers' burden is very likely to determine the elderly institutionalization. Multiple hospital admissions preceding institutionalization are also very common.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior research demonstrated that individuals and families are in need of education and information about AD [12, 13]. An analysis of the Porter Novelli Health Styles survey data indicated that close to 30 % of consumers have searched specifically for cognition and AD-related information online [14].…”
Section: Introductionmentioning
confidence: 99%